Criminal Sanctions for Corruption in Islamic and Positive Legal Systems: A Comparative Study of Indonesia, Saudi Arabia, and Egypt - Faishal Agil Al Munawar (PT. Riset Press International, 2026)
Corruption constitutes a serious criminal offense that undermines legal integrity, social justice, and the sustainability of national development. Beyond its characterization as a violation of positive law, corruption also represents a profound breach of moral values and public trust (amanah) within the framework of Islamic law. This article aims to comparatively analyze criminal sanctions for corruption under Islamic law and positive law, with particular focus on Indonesia, Saudi Arabia, and Egypt. The study adopts a normative juridical methodology employing a comparative law approach, examining statutory regulations, doctrines of Islamic criminal law (fiqh jināyah), and relevant contemporary legal literature. The findings demonstrate that, within Islamic law, corruption is classified as a jarīmah ta‘zīr, as its sanctions are not explicitly stipulated in the primary sources (naṣṣ). Consequently, discretionary authority is vested in rulers or judges to determine appropriate penalties based on considerations of public welfare and social harm. In contrast, Indonesia regulates corruption through comprehensive and specialized anti-corruption legislation, emphasizing imprisonment, fines, and supplementary sanctions such as asset confiscation and the revocation of certain rights. Saudi Arabia implements a criminal law framework grounded predominantly in Islamic law and reinforced by modern regulatory instruments, imposing relatively severe sanctions designed to ensure deterrence and safeguard public trust. Meanwhile, Egypt applies a civil law–based legal system, criminalizing corruption through codified provisions in the Penal Code and specialized anti-corruption statutes. This study concludes that, notwithstanding conceptual and structural differences in the regulation of corruption sanctions, both Islamic law and positive law converge on shared objectives, namely the preservation of justice, the prevention of social harm, and the protection of public interests. The integration of ethical values and the principles of maqāṣid al-sharī‘ah into positive legal systems offers significant potential to enhance the coherence, legitimacy, and long-term effectiveness of anti-corruption frameworks.